A Framework for the Evaluation of Biosecurity, Commercial, Regulatory, and Scientific Impacts of Plant Viruses and Viroids Identified by NGS Technologies - Massart, Sebastien; Candresse, Thierry; Gil, José; Lacomme, Christophe; Predajna, Lukas; Ravnikar, Maja; Reynard, Jean-Sébastien; Rumbou, Artemis; Saldarelli, Pasquale; Škorić, Dijana; Vainio, Eeva J.; Valkonen, Jari P. T.; et al. (Frontiers in Microbiology, 2017)
Recent advances in high-throughput sequencing technologies and bioinformatics have generated huge new opportunities for discovering and diagnosing plant viruses and viroids. Plant virology has undoubtedly benefited from these new methodologies, but at the same time is also faced with substantial bottlenecks, namely the biological characterization of the newly discovered viruses and the analysis of their impact at the biosecurity, commercial, regulatory and scientific levels. This paper proposes a scaled and progressive scientific framework for efficient biological characterization and risk assessment when a previously known or a new plant virus is detected by next generation sequencing (NGS) technologies. Four case studies are also presented to illustrate the need for such a framework, and to discuss the scenarios.